2016
DOI: 10.1155/2016/6469240
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cervical Cancer Screening Uptake among Women in Ilorin, North Central Nigeria: A Community-Based Study

Abstract: Introduction. Cancer of the cervix is the leading cause of cancer deaths among women in developing countries. Screening is one of the most cost effective control strategies for the disease. This study assessed the determinants of cervical cancer screening uptake among Nigerian women. Methodology. This cross-sectional study was conducted using multistage sampling technique among 338 participants in Ilorin, North Central Nigeria. A pretested questionnaire was used for data collection and data analysis was done u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
53
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 17 publications
14
53
4
1
Order By: Relevance
“…[ 2 , 5 – 9 ] Indeed, since the introduction of the Papanicolaou smear cytology testing in the 1950s and 1960s, cervical cancer incidence and mortality have declined in the United States with organized cervical cancer screening programs and screening rates of 83%. [ 10 – 12 ] However, Cervical cancer remains a huge burden in developing countries where cervical cancer screening rates are currently low, ranging between 6–8% [ 13 , 14 ] These disparities in screening rates and HPV vaccination coverage might explain the differences in incidence and mortality associated with cervical cancer in different regions around the world.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 5 – 9 ] Indeed, since the introduction of the Papanicolaou smear cytology testing in the 1950s and 1960s, cervical cancer incidence and mortality have declined in the United States with organized cervical cancer screening programs and screening rates of 83%. [ 10 – 12 ] However, Cervical cancer remains a huge burden in developing countries where cervical cancer screening rates are currently low, ranging between 6–8% [ 13 , 14 ] These disparities in screening rates and HPV vaccination coverage might explain the differences in incidence and mortality associated with cervical cancer in different regions around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Distance could have been a major deterrent as 50% of the camps were 40 km away from the health facilities. In a study conducted in a Nigerian community, the reasons reported for nonparticipation in the screening program were fear of cancer diagnosis, disagreement of the husband, perception of low risk, negative attitude toward cervical cancer screening, and fear of being perceived as promiscuous [27]. Although, the reasons are yet to be understood in Indian context, this evidence underlines the significance of educating the rural population, both men and women, about the advantages of cervical cancer screening [28,29].…”
Section: Discussionmentioning
confidence: 97%
“…Utilisation of cervical cancer screening services is low, especially in lower socio-economic communities and rural areas. [ 15 , 16 , 17 , 18 ] There is a need to understand women’s motivation and factors affecting utilisation of services. [ 19 ] This study will contribute to a better understanding of the barriers to cervical cancer screening among women with HIV in Botswana.…”
Section: Introductionmentioning
confidence: 99%